Pola Spasial Tingkat Rawan Kekeringan Hidrologis Pada Lahan Padi di Kota Semarang: - - Galih Langit Pamungkas; Zaki Kresna Andika (Stasiun Pemantau Atmosfer Global Lore Lindu Bariri - Palu, 2021)
Semarang City has various kinds of superior commodities, one of which is the rice fields. However, the danger of lack of groundwater availability due to hydrological drought has always been a major problem for the quality of rice production. Therefore, this research aims to determine the distribution of groundwater availability in the area of ​​Semarang City which is suitable for rice crops. The weighted drought hydrology method used in this study is a new applied method in Semarang with Thornthwaite – Matter method to see the amount of groundwater available each month by its rainfalls. Other data used are physical data of land and elevation. The results show that the level of mild drought prone (<16.77%) in Semarang City occurs in the southern area of ​​the city in January, February and March. Meanwhile, severe drought – prone areas (>33.33%) occurs in the northern area of ​​Semarang City in August, September and October. So, we know that the southern area of ​​Semarang City is more suitable for rice production than the northern area of ​​the city.